MATHEMATICS AND ISLAMIC MODERATION: INTERNALISING THE VALUE OF TAWWASUTH ON THE MATERIAL OF LINEAR EQUATIONS ONE VARIABLE - Muhammad Ilman Nafi’an (Jurnal Media Akademik (JMA), 2024)
Internalising Islamic moderation values especially tawwasuth in mathematics is very important in mathematics education, because it can equip moderate characters and avoid extreme ideologies in Indonesia, but there are still few studies that discuss this, this study aims to internalise the value of tawwasuth on the concept of linear equations. This research is a literature research with an analogy strategy. Reviewing theories, references and other scientific literature related to mathematics and tawasuth. The result of this research is that solving linear equations focuses on finding values that equalise both sides of the equation. It involves finding the values of variables to form the solution set. The basic principle is to achieve a balance between the two sides of the equation, as in the concept of tawasuth in Islam, promoting moderation and harmony. The importance of moderate character is emphasised in mathematics learning, encouraging inclusiveness and preventing extremism, to form a peaceful and tolerant society.